ANALYSIS OF PROJECT AND OPERATION OF WASTEWATER TREATMENT PLANT IN CRAVINHOS, SP, BRAZIL - Vieira, Elias Antonio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611704375 The present study deals with the procedure employed by the author in the evaluation ofa project to establish Wastewater Treatment Plant – WWTP in Cravinhos (SP). The method usedconsisted of a literature review and analysis of project documentation. The aim of this work is tosupport those interested in understanding the functioning of this type of project, as well ascontributing to the resolution of their faults. The results of this study indicated weaknesses andunconformities in the project in relation to the operation of the WWTP.